Battery Cells for Electric Vehicles - Halimah, Putri; Rahardian, Samuel; Budiman, Bentang (http://dx.doi.org/10.31427/IJSTT.2019.2.2.3, 2019)
The shifting trend of conventional to the electric drivetrain in automotive industries makes batteries become the most favorable energy storage. There are three types of battery cells that are commonly used for electric vehicles i.e., cylindrical cells, pouch cells, and prismatic cells. The use of active material such as lithium-ion in the battery of electric vehicles could bring some issues related to the safety field. For that reason, comprehensive research on battery failure analysis needs to be conducted. This paper reviews the recent progress of the use of battery cells in electric vehicles and some challenges which must be considered to assure their safety. There are a lot of studies on battery failure analysis, which mainly focuses on the appearance of a short circuit as the main cause of the thermal runaway event. Several proposals on predicting short circuits in the battery due to various loading are comprehensively discussed. Those research results can be considered to establish regulations in designing battery protectors.